A GIS-based study on the estimation of fixed atmospheric CO2 in tropical tree biomass from Neyyar Wildlife Sanctuary, South India. Issue 4 (2nd October 2019) - Chrips, Nesayyan R.; Razafindrabe, Bam H.N.; Williams, Ben C.; Vinod, Raghavakurup T.
ABSTRACT: This study aims to estimate the fixed CO2 in tree biomass in the Neyyar Wildlife Sanctuary in Western Ghats, India. The methodology consists of a GIS-based estimation of atmospheric CO2, based on the Food and Agriculture Organization (FAO) estimation method. Prior to further analyses such as satellite image classification processes, radiometric and geometric corrections were conducted to remove unwanted artefacts, such as additive effects due to atmospheric scattering, using a set of preprocessing or clean-up routines. Tree vegetation categories – dense evergreen, evergreen, dense semi-evergreen, semi-evergreen, and moist deciduous – were identified. Tree formations were also categorized based on their elevation: high elevation, medium elevation, and low elevation. Findings showed that fixed CO2 per unit area (1 ha) ranged from 356.98 t for high elevation dense evergreen to 205.24 t for low elevation semi-evergreen vegetation. Different elevation ranges in those tree formations also displayed distinct differences in the fixed CO2 per unit area. For dense evergreen formation, fixed CO2 was highest at high elevation, lowest at medium elevation. Evergreen and dense semi-evergreen showed higher values at low elevations compared to those at medium elevations. In semi-evergreen and moist deciduous, medium elevation trees showed higher values than those at low elevations.